(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This study seeks the critical analysis of the Supreme Federal Court’s decision in ADO (unconstitutionality action for omission) No. 26. Initially, the court’s history and arguments are presented. Then it is held critically about the possible violation of the legality principles and of the separation of powers, based on decisions of the court itself, arguments and criticisms of renowned thinkers. Subsequently, the Constitutional Dialogues theory is analyzed, tracing possible paths for the Democratic State of Law to follow, in order to make better reasoned decisions and that materialize the Constitution’s previsions. Finally, it is possible to conclude that the Supreme Federal Court’s decision in ADO No. 26, violated the principles of legality and separation of powers.